Novel insight into the microstructure evolution and strengthening mechanism of nanocrystalline copper prepared by hot-pressing sintering: A molecular dynamics study - Qianwen Feng; Xiang Zhang (AIP Advances)
An integrated strategy is proposed for the design and performance evaluation of nanocrystalline (NC) copper prepared by using the hot-pressing sintering process (HPS). Molecular dynamics (MD) simulation is employed to investigate the microstructure and performance of the prepared NC copper. The merging of nanoparticles (NPs) during HPS is influenced by the initial surface area of NPs. A higher surface area corresponding to a smaller size of NPs will promote the merging of NPs by providing more interface for the diffusion of atoms. The designed grain size can be obtained by adjusting the initial size of NPs. The mechanical properties of NC copper do not present a liner correlation with the grain size. With the grain size increasing from 1.51 to 4.10 nm, the strength and ductility of NC copper first increase but then decrease. The cooperating influence of the grain boundaries with high strength and the matrix with high ductility on the mechanical properties is revealed. This study highlights the relationship between microstructure evolution and mechanical properties in NC metals, offering insights into designing high-performance NC materials. The MD model can be extended into another case with a larger size and time scale.